ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN (GREEN ACCOUNTING) MENURUT PERSPEKTIF ISLAM DALAM PENGELOLAAN LIMBAH PADA PT. SUMBER GRAHA SEJAHTERA - Liza Tania; Rafidah Rafidah; Faturahman Faturahman (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The results of the study show the application of environmental accounting (Green accounting) according to the Islamic perspective of waste management of PT. Sources of Graha Sejahtera (SGS) include Avoiding Air Pollution, Good Waste Management and Green Spaces. PT incurs costs for environmental activities such as waste management, environmental monitoring costs, employee training costs, and environmental activity audit costs. All environmental costs, and allocating these costs based on cost types in a structured environmental accounting contribute well to environmental performance. The impact of the application of environmental accounting in waste management at PT. Sumber Graha Sejahtera (SGS) produces goodness and cleanliness because when a company carries out activities support environmental management, the management must wisely record every cost incurred related to environmental activity. These costs are referred to as environmental costs that must be charged to functions within the company appropriately, for example, production functions, marketing functions and other functions.